Learning Devices in the Unit of Education - Melisa Rezi; Muhammad Husni Shidqi; Ahmad Firdaus bin Mohd Noor (Al-Hijr: Journal of Adulearn World, 2022)
The purpose of this study was to explore the learning tools used in the educational environment. In this study, the researcher used a survey method with reference to research conducted by previous researchers. The object of research being carried out is all learning tools such as effective week analysis, lesson plans, annual programs, semester programs, syllabus, and KKM. Learning tools are very helpful for teachers in carrying out educational programs, especially in teaching and learning activities. Learning tools are something that is very important in an educational unit.